Bridging the Divide. An Interdisciplinary Analysis of Trust in Science - Gökçe Zeybek Kabakci; Umut Yener Kara; Gökçe Baydar Çavdar; Emre Toros (Sage Open, 2025)
For several reasons, trust in science in recent years has eroded, throwing serious doubts on once-reliable scientific resources. Although multiple scientific disciplines try to explain the causes and consequences of this worrying decline, we have only scant knowledge about these disciplines' interconnected arguments. Focusing on this niche, this study aims to bridge the literature from diverse academic disciplines and identify dominant themes by utilising a cutting-edge methodology. This attempt is crucial since we need a comprehensive understanding of the complex factors influencing public trust in science, allowing us to approach the problem from multiple angles and enabling the crafting of evidence-based policies that better resonate with the public and are more likely to be effective in restoring trust. Hence, this study contributes to the existing literature both substantially and methodologically. Substantially, we show that there are dominant recurring research themes across the disciplines, such as science communication, compliance with scientific advice, and public engagement. Methodologically, we contend that identifying these vital crosscutting themes can only be possible by combining state-of-the-art computational techniques with conventional qualitative content analysis.
Keywords: 300; communication studies; communication; social sciences; trust; science; trust in science; interdisciplinary; text mining; network analysis